Morphological variation in Musa germplasm - Ortíz, R. (Springer, 1997)
Musa cultivars (bananas and plantains) are important crops in the humid tropics of Africa, America and Asia. This paper reports the extent of morphological variation of the Musa germplasm maintained in the gene-bank of the International Institute of Tropical Agriculture in southeastern Nigeria. Qualitative and quantitative descriptors were used to evaluate AA, BB, AB, AAA, AAB, AAAA, AAAB and AABB bananas, AAA and ABB cooking bananas, AAA beer bananas and AAB plantains and a few wild species. Univariate and principal component (PCA) analyses were performed to identify the most important descriptors to characterize and classify Musa germplasm collections. The most important qualitative morphological descriptors were persistence of male bud and hermaphrodite flowers, pigmentation in pseudostem, foliage, petiole and male flower, pseudostem blotching and waxiness, and leaf orientation. Furthermore, the most important quantitative morphological descriptors included pseudostem girth, height of tallest sucker, number of fruits and fruit sizes. These quantitative descriptors have a high heritability (>0.8), high repeatibility (>2.0) and low coefficient of variation (9–15%) with the exception of the height of the tallest sucker. The implications of the germplasm grouping revealed by PCA are briefly discussed in relation to the evolution of the triploid cultivars. This paper also proposes a new scientific nomenclature for the triploid Musa cultivars.